Magnesium hydroxide derivatives as stabilisers and flame retardants for plasticised poly (vinyl chloride) - Labuschagne, F.J.W.J. (Frederick Johannes Willem Jacobus) (University of Pretoria, 2016)
Thesis (PhD)--University of Pretoria, 2015.